Otitis media with effusion: an effort to understand and clarify the uncertainties - Chantzi, F. M.; Bairamis, T.; Papadopoulos, N. G.; Kafetzis, D. A. (Expert Rev Anti Infect Ther, 2005)
Otitis media with effusion–defined as the accumulation of middle-ear effusion behind an intact tympanic membrane without signs or symptoms of acute infection–is one of the most common causes of hearing loss in children in developed countries, potentially leading to language deficits. Although treatment of chronic or relapsing otitis media with effusion is considered imperative, none of the preventative or nonsurgical management measures currently available have proven effective. Tympanostomy tube placement remains the recommended treatment option for high-risk children or for cases of unresponsive otitis media with effusion. This can be attributed to the uncertainties surrounding its pathogenesis. Multiple factors and several possible pathogenetic models have been proposed to explain the production and persistence of middle-ear effusion; only a few of them are supported by sufficient evidence. In this review, the authors will present current knowledge on the pathogenesis, consequences, diagnosis and management of otitis media with effusion. An effort will be made to clarify those aspects sufficiently supported by evidence-based studies, and to underline those that remain unfounded.
Keywords: Hearing Loss Humans Otitis Media with Effusion